2020
DOI: 10.1186/s12884-020-03324-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal excessive gestational weight gain as a risk factor for autism spectrum disorder in offspring: a systematic review

Abstract: Background Abnormal gestational weight gain (GWG) is a prenatal complication that may contribute to long-term behavioral and neurodevelopmental differences in offspring. This systematic review summarizes research on the association between maternal GWG and risk of autism spectrum disorder (ASD) in offspring. Methods Google and electronic databases, including PubMed, SCOPUS, Embase, Cochrane Library and Google Scholar, were searched for original human studies published in English through June 2020. Articles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Epidemiologic studies identify increased ASD risk associated with pre-pregnancy obesity ( 46 ) and/or gestational weight gain ( 2 , 12 , 56 ). Obesity promotes both inflammation and endocrine dysfunction, perturbing the prenatal environment.…”
Section: Obstetric Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologic studies identify increased ASD risk associated with pre-pregnancy obesity ( 46 ) and/or gestational weight gain ( 2 , 12 , 56 ). Obesity promotes both inflammation and endocrine dysfunction, perturbing the prenatal environment.…”
Section: Obstetric Conditionsmentioning
confidence: 99%
“…The placenta also influences fetal HPA axis maturation through its production of CRH (pCRH). pCRH stimulates fetal adrenal DHEA(S) production by ( 1 ) signaling fetal pituitary ACTH release ( 143 ), ( 2 ) heightening fetal adrenal gland sensitivity to ACTH ( 144 ), and ( 3 ) stimulating DHEA(S) producing fetal adrenal cells directly ( 145 , 146 ). By increasing fetal DHEA(S) synthesis, pCRH facilitates increased placental estradiol production.…”
Section: Fetal Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiological factors of ASD remain largely unknown. However, it has been reported that risk factors, such as genetics, environmental factors, prenatal and perinatal factors, are involved in the development of ASD ( 6 ). Among these, genetics occupies the main factor.…”
Section: Introductionmentioning
confidence: 99%
“…The etiological factors of ASD remain largely unknown. But it has been reported that risk factors, such as genetics, environmental factors, prenatal and perinatal factors are involved in the development of ASD [6] .…”
Section: Introductionmentioning
confidence: 99%